Smooth dynamical systems - Irwin, M. C. (Michael Charles), 1934- (Advanced series in nonlinear dynamics ;, 2001)
This is a reprint of M C Irwin's beautiful book, first published in 1980. The material covered continues to provide the basis for current research in the mathematics of dynamical systems. The book is essential reading for all who want to master this area. Request Inspection Copy. Contents: Some Simple Examples; Equivalent Systems; Integration of Vector Fields; Linear Systems, Linearization, Stable Manifolds; Stable Systems; Appendices. Readership: Graduate students in mathematics.